Professorial Advancement Initiative: A Cross-Institutional Collaboration to Increase Faculty Diversity in STEM - Yadav, Aman; Smith, Mark J. T.; Farber, Charity Rae; Mason, Linda J. (Frontiers in Psychology, 2021)
In this paper, we describe the model for faculty diversity developed as part of the Professorial Advancement Initiative (PAI) funded under the NSF AGEP program. The PAI, consisting of 12 of the 14 Big Ten Academic Alliance universities,1 had the goal of doubling the rate at which the universities hired tenure-track minoritized faculty, defined by National Science Foundation as African Americans, Hispanic/Latinx, Native Americans, and Pacific Islanders. This paper reviews the key programmatic elements of the PAI and discusses lessons learned and the practices developed that helped the Alliance achieve its faculty diversity goal.